Transmission conditions for a soft elasto-plastic interphase between two elastic materials. Plane strain state - Mishuris, G.; Öchsner, A. (Archives of Mechanics, 2005)
A thin interphase between two different elastic media is under consideration. It is assumed that the intermediate layer consists of a soft elasto-plastic material whose Young’s modulus is small enough in comparison with those of the bounding materials. Using an asymptotic technique, nonlinear transmission conditions for the bimaterial structure are evaluated. As a numerical example, a FEM analysis of a bimaterial structure with an interface is performed to investigate the accuracy of the derived transmission conditions.